Optimization of spray drying conditions for production of quality pomegranate juice powder - Khalid Muzaffar (Cogent Food & Agriculture, 2016)
The present study was aimed to optimize the spray drying operating parameters for the production of quality pomegranate juice powder using response surface methodology. The spray drying operating conditions including inlet air temperature (170–190°C), feed flow rate (18–30 mL/min), and blower speed varied (2,000–2,400 rpm) were used as independent variables. The responses evaluated were ascorbic acid content, anthocyanin content, moisture content, hygroscopicity, and water solubility index. Statistical analysis showed that among the independent variables, inlet air temperature showed greater effect on all the investigated responses. The derived optimum conditions were used for the powder production to check the validity of the quadratic model. Small deviations were observed between the experimental values and the predicted ones and the values were within the acceptable limits. The results showed that the optimum spray drying operating conditions for the production of pomegranate juice powder with optimum quality were 171°C inlet temperature, 30 mL/min feed flow rate, and 2,400 rpm blower speed. Under these optimum conditions, quality pomegranate juice powder with desirable properties of high content of vitamin C and anthocyanin, low moisture content, low hygroscopicity, and high solubility could be produced.